Integrasi Political Listening dan Micro-Targeting Digital: Studi Kasus Strategi Pemasaran Politik Progresif Zohran Mamdani - Mahardhikka Prakasha Shatya (Journal of Innovative and Creativity, 2026)
​This research analyzes Zohran Mamdani's political marketing strategy in the New York City Mayoral election, where he successfully garnered constituent support despite the dominance of political dynasties and oligarchies. Utilizing a descriptive qualitative approach and a single case study design, this study explores how the integration of political listening and digital micro-targeting creates an electoral advantage. The results indicate that Mamdani effectively implemented the Market-Oriented Party (MOP) model by prioritizing marginal issues, such as the housing crisis, through intensive grassroots interaction. Furthermore, the use of social media algorithms and micro-targeting allowed progressive political messages to precisely reach specific voter segments, such as immigrant communities and the younger generation. These findings emphasize that contemporary political success depends on a feedback loop between practical action, field observation, and academic analysis capable of validating political market expectations.